2013
DOI: 10.1002/er.3120
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of thermal behaviour of biomass and coal during copyrolysis using thermogravimetric analysis

Abstract: SUMMARYThe biomass, coal and their blends at blending ratios (biomass : coal) of 95:5, 90:10, 85:15 and 80:20 were pyrolysed under a nitrogen environment at four different heating rates comprising 5°C, 10°C, 15°C and 20°C per minute to investigate their pyrolytic behaviour and to determine kinetic parameters of thermal decomposition through Kissinger's corrected kinetic equation using the thermogravimetric analysis results. In the kinetic analysis, the activation energy of both types of biomass was less than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…Several researchers reported that the volatiles yields exceeded the expected values calculated from individual samples based on additive behavior during co-pyrolysis, which can be named as synergistic effects [13][14][15][16][17]. Nevertheless, some researchers were against the presence of synergistic effects during co-pyrolysis [8,18]. To summarize, it seems that there is no general regulations that can be used to predict thermal behavior of biomass and coal in their co-pyrolysis process.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several researchers reported that the volatiles yields exceeded the expected values calculated from individual samples based on additive behavior during co-pyrolysis, which can be named as synergistic effects [13][14][15][16][17]. Nevertheless, some researchers were against the presence of synergistic effects during co-pyrolysis [8,18]. To summarize, it seems that there is no general regulations that can be used to predict thermal behavior of biomass and coal in their co-pyrolysis process.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have been focused on the thermal behavior and kinetic analysis of a variety of coals blended with different biomasses, such as sawdust [7], cypress wood chips [8], and pine chips [9] from forestry residues, cherry pit [10], hazelnut shell [11], sugar beet pulp [12], straw [13], corn and sugarcane [14] from agricultural residues. However, due to the great varieties and heterogeneity of biomass, different conclusions on the thermal behavior were obtained by different researchers.…”
Section: Introductionmentioning
confidence: 99%
“…This value is higher than that of biomass and coal which range between 50 and 180kJ/mol and 30 and 90 kJ/mol respectively. This corresponds to the biomass of cypress wood chips and macadamia nut shells as observed by Vhathvarothai et al (2013), that the value was 168.7kJ/mol and 164.5kJ/mol respectively (N. Vhathvarothai et al, 2013). This shows that MSW need high energy to react as compared to biomass and coal.…”
Section: Dtg Curvesmentioning
confidence: 68%
“…Kinetics analysis methods were used to study the carbon dioxide gasification of nascent oil shale, bitumite, lignite, and the blends of oil shale with other two types of coals. The rate of fuel's conversion, dα / dt , is the linear function of a temperature‐dependent rate constant and function of conversion, which is described as k ( T ) and f ( α ), respectively , dαtrue/dt=k()Tf()α where α is the conversion degree, t (s) is experimental time, T (K) is the absolute temperature, k (T) usually described by the Arrhenius equation, k=Aexp()prefix−Etrue/RT where A (s −1 ) is pre‐exponential Arrhenius factor, E (kJ/mol) is the apparent activation energy, R (kJ/mol K) is the universal gas constant.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics analysis methods were used to study the carbon dioxide gasification of nascent oil shale, bitumite, Gasification characteristics of fossil fuels S. Li and X. Ma lignite, and the blends of oil shale with other two types of coals. The rate of fuel's conversion, dα/dt, is the linear function of a temperature-dependent rate constant and function of conversion, which is described as k(T) and f(α), respectively [25,26],…”
Section: Kinetic Theorymentioning
confidence: 99%